2007
DOI: 10.1253/circj.71.191
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Subclinical Thyroid Dysfunction From Cardiovascular and Metabolic Viewpoints The Suita Study

Abstract: ubclinical hypothyroidism (SCH), defined as high serum thyroid-stimulating hormone (TSH) levels and normal levels of serum free-triiodothyronine (fT3) and serum free-thyroxine (fT4), is a common medical problem among the elderly. The prevalence of SCH has been reported to be 4-10% in the general population and up to 20% in women older than 60 years. [1][2][3] The incidence of SCH is 2.1-3.8% per year in thyroid-antibody-positive subjects and 0.3% per year in thyroid-antibody-negative subjects. 4 Serum lipid le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
69
5
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 17 publications
10
69
5
6
Order By: Relevance
“…There are some other reports that studied in smaller number of patients with dyslipidemia and reported 6.8% (2.2% and 4.6%, overt hypothyroidism and subclinical hypothyroidism, respectively) in United Kingdom [6], 7.8% (2.5% and 5.3%) in United States [7], and 7.2% (2.8% and 4.4%) in Greece [9]. Thus, the percentage in our study was comparable to previous studies in the subjects with dyslipidemia, but not as high as that in the studies recently reported in Japanese population [25,26]. Several reasons can be described.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…There are some other reports that studied in smaller number of patients with dyslipidemia and reported 6.8% (2.2% and 4.6%, overt hypothyroidism and subclinical hypothyroidism, respectively) in United Kingdom [6], 7.8% (2.5% and 5.3%) in United States [7], and 7.2% (2.8% and 4.4%) in Greece [9]. Thus, the percentage in our study was comparable to previous studies in the subjects with dyslipidemia, but not as high as that in the studies recently reported in Japanese population [25,26]. Several reasons can be described.…”
Section: Discussionsupporting
confidence: 85%
“…Several reasons can be described. First of all, we performed multi-center study whose institutions distribute all over Japan, whereas Nagasaki [25] or Suita [26] is a single city. In addition, there are some resources to obtain the clinically important frequency of subclinical hypothyroidism in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, 18 of the 29 examined studies considered an upper-limit TSH value of over 4 mU/l. This variability in limits might explain the lack of association between BMI and TSH in 11 (5,9,13,16,19,23,25,28,29,33,40) of the 29 examined studies. Another source of discrepancy is the fact that almost half of the studies did not perform adjustment for potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…SCH is defined as a mild elevation of TSH and normal levels of free thyroid hormones. The association between SCH and individual cardiovascular risk factors has also been explored, with discordant results (4)(5)(6). Even more controversial is the association between SCH and insulin resistance (7).…”
Section: Introductionmentioning
confidence: 99%
“…If free thyroxine (FT 4 ) levels are considered, they are generally used only to define normality. Recently, Ross and coworkers reported a significant association between FT 4 levels and the components of the metabolic syndrome (MS) in euthyroid patients (8).…”
Section: Introductionmentioning
confidence: 99%